Guidelines on fatigue life of aging pressure vessels. (Energy Institute, 2019)
This publication assists plant engineers in determining the risk of fatigue failure of their pressure vessels and helps them to assess the remaining fatigue life and/or plan targeted cost-efficient inspections or other measures for vessels most at risk. It provides advice on the assessment of remaining fatigue life using modern analysis methods and suggests ways in which further service beyond a calculated fatigue usage of unity may be justified and the fatigue life of welds improved. These guidelines are written with vessels on offshore oil and gas installations in mind, but are expected to be of wider application as many similar vessels remain in service at on-shore installations, chemicals plants and in other industrial sectors.